Working Women Worldwide. Age Effects in Female Labor Force Participation in 117 Countries. (October 2015) - Besamusca, Janna; Tijdens, Kea; Keune, Maarten; Steinmetz, Stephanie
Highlights: We study labor force participation rates of women in 11 age groups in 117 countries. Sector sizes and per capita GDP affect the timing of labor market entry and exit. Women between 25 and 55 years of age are more likely to work when paid maternity leave schemes exist. Enrollment in pre-primary education increases the FLPR of women between 25 and 55 years. Higher religious adherence is associated with lower FLPR of women between 25 and 55 years of age. Summary: In this article, we investigate the effects of economic conditions, families, education, and gender ideologies on the labor force participation rates of women in eleven age groups in 117 countries. We find that participation rates of young and older women are partly explained by sector sizes and the level of economic development. However, to explain the labor force participation rates of women between 25 and 55 years, we need to study families and gender ideologies. We find these women are more likely to participate when paid maternity leave schemes exist, enrollment in pre-primary education is higher, and countries are less religious.